2019
DOI: 10.1163/15685411-00003270
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pasteuria penetrans on different field populations of Meloidogyne spp. from Pakistan

Abstract: SummaryPasteuria penetrans is a hyperparasite with potential as a biological control agent of root-knot nematodes, Meloidogyne spp. In this study two exotic Pasteuria isolates (PP-3 and PP-J) were developed on different Meloidogyne spp. collected from different districts of Punjab, Pakistan. The development of PP-3 and PP-J on different field populations of Meloidogyne spp. showed differential infectivity in terms of nematode reproduction variables. The development of PP-3 and PP-J was maximum on tomato as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The OD formulation very effective due to the fact that the oil OD formulation only took one day to degrade completely in soil and had a faster mode of action in soil than other formulations. This was in accordance with Weibelzahl- The yield parameters were higher in OD formulation treated plants that is supported by the ndings of These observations were similar with the e cacy test of P. penetrans on M. incognita reproduction in tomato which was documented by Kamran et al (2014). Vagelas and Leontopoulos (2022) reported that mobility of nematodes was arrested and capability to locate host was affected when the nematodes encumbered with spores of P. penetrans and failure of reproductive organs in adult nematodes which lead to reduce production of next generation of nematode.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The OD formulation very effective due to the fact that the oil OD formulation only took one day to degrade completely in soil and had a faster mode of action in soil than other formulations. This was in accordance with Weibelzahl- The yield parameters were higher in OD formulation treated plants that is supported by the ndings of These observations were similar with the e cacy test of P. penetrans on M. incognita reproduction in tomato which was documented by Kamran et al (2014). Vagelas and Leontopoulos (2022) reported that mobility of nematodes was arrested and capability to locate host was affected when the nematodes encumbered with spores of P. penetrans and failure of reproductive organs in adult nematodes which lead to reduce production of next generation of nematode.…”
Section: Discussionsupporting
confidence: 88%
“…Fulton et al (1996) who tested the e cacy of P. penetrans against M. incognita and M. javanica in tobacco plant. The biocontrol potential of P. penetrans proved by several authors(Mukhtar et al, 2013;Kamran et al, 2014;Kumari, 2017) in various crops Tzortzakakis et al (1997). conducted the interaction study between P. penetrans and M. incognita under pot culture condition.…”
mentioning
confidence: 99%